Relation of oxygen uptake to work rate in prepubertal healthy children – reference for VO2/W‐slope and effect on cardiorespiratory fitness assessment. (9th August 2017) - Tompuri, Tuomo; Lintu, Niina; Laitinen, Tomi; Lakka, Timo A.
Summary: Purpose: Exercise testing by cycle ergometer allows to observe the interaction between oxygen uptake (VO2 ) and workload (W), and VO2 /W‐slope can be used as a diagnostic tool. Respectively, peak oxygen uptake (VO2 PEAK ) can be estimated by maximal workload. We aim to determine reference for VO2 /W‐slope among prepubertal children and define agreement between estimated and measured VO2 PEAK . Methods: A total of 38 prepubertal children (20 girls) performed a maximal cycle ergometer test with respiratory gas analysis. VO2 /W‐slopes were computed using linear regression. Agreement analysis by Bland and Altman for estimated and measured VO2 PEAK was carried out including limits of agreement (LA). Determinants for VO2 /W‐slopes and estimation bias were defined. Results: VO2/W‐slope was in both girls and boys ≥9·4 and did not change with exercise level, but the oxygen cost of exercise was higher among physically more active children. Estimated VO2 PEAK had 6·4% coefficient of variation, and LA varied from 13% underestimation to 13% overestimation. Bias had a trend towards underestimation along lean mass proportional VO2 PEAK . The primary determinant for estimation bias was VO2/W‐slope (β = −0·65; P <0·001). Conclusion: The reference values for VO2 /W‐slope among healthy prepubertal children were similar to those published for adults and among adolescents. Estimated and measured VO2 PEAK should not be considered to be interchangeable because of the variation in the relationship between VO2 and W. On other hand, variation in the relationship between VO2 and W enables that VO2 /W‐slope can be used as a diagnostic tool.